Constraining the age of the Côa valley (Portugal) engravings with radiocarbon dating - Dorn, Ronald I.
Radiocarbon ages for the Côa petroglyphs are very similar to those obtained by Watchman (1995). Fundamental problems in the use of radiocarbon dating at Côa include evidence for the addition of younger carbon in an open system, and evidence of contamination from older sources of carbon. Radiocarbon measurements, therefore, cannot be used to decide whether the engravcings are or are not of Palaeolithic age.